Understanding Drishti in the lights of Netra Sharir and various Ocular disorders - A Review - Mehar, Kapil; Tripathi, Ankur; Bavalatti, Narayan; Rajagopala, Manjusha (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Ayurveda, the most ancient science of life, is loaded with lots of complex terminologies. To have expertise in learning and treating any disease, one must be well-versed in understanding these terminologies and their relevant meaning. Such is the term Drishti less defined in the context of Structure, Dimensions, Morphology etc., but diversely mentioned in several contexts, which makes it very difficult to confine Drishti to any single specific part of the eyeball. Material and Methods: The correlation of the term Drishti with the various entities of the eyeball has been done by in-depth analysis of various Sanskrit and English dictionaries, classical texts of Ayurveda along with commentary as well as texts from modern science. Result: The Drishti is not only a physical entity but also possesses functional property too. The structures coming in the visual axis of the eye and their functional integrity in toto can be taken as Drishti. Conclusion: The term ‘drishti’ used in Ayurveda has a deep and broad meaning and should be interpreted in accordance to the context.